FEATURES OF THE DIGITALIZATION OF THE FOREIGN ECONOMIC ACTIVITIES OF ENTERPRISES UNDER THE CONDITIONS OF THE MILITARY STATE - Савчук, Світлана (Scientific Bulletin of Ivano-Frankivsk National Technical University of Oil and Gas (Series: Economics and Management in the Oil and Gas Industry), 2024)
The article examines theoretical and methodological approaches to determining the features of digitization of foreign economic activities of enterprises under martial law. The main tasks of the article are the analysis of the influence of the state of war on the effectiveness of the management of foreign economic processes, the determination of the key advantages and risks that arise in the context of digitalization, as well as the development of recommendations for the optimization of digital transformations to ensure the sustainable and competitive development of enterprises in the difficult conditions of wartime. A wide range of problems, challenges, threats arising in the functioning of foreign economic activity in Ukraine in the context of today's complex situation were considered, which can be grouped as follows: problems related to the security of industry and risks of terrorism, problems related to human capital, problems related to logistics and infrastructure of foreign economic activity, legal problems. It was established that the export of goods and services decreased by 58% over the last 2 years (during the war), while the import of goods and services decreased by 30%. It has been proven that there is a need to implement a number of measures to promote the development of foreign economic activity, and one of the key areas that is gaining importance is the implementation of digital initiatives and tools. The advantages of implementing digital solutions in the field of foreign economic activity at the enterprise level (increasing the efficiency of management, improving logistics, adapting to the changing conditions of the external environment, reducing operating costs, etc.) and at the state level (reducing bureaucratic obstacles, reducing corruption, improving the efficiency of customs control) have been identified , simplifying access to global markets, etc.). Despite the fact that digital technologies have many positive points, it is justified that there are also a number of problems: increasing cyber threats, the need for significant financial investments and highly qualified personnel. Thus, the digitalization of the foreign economic activity of enterprises under martial law is a key factor for ensuring their stability, adaptability and efficiency in crisis situations.